Role of vitamin K2 in bone metabolism: a point of view and a short reappraisal of the literature. (2nd April 2020) - Capozzi, A.; Scambia, G.; Migliaccio, S.; Lello, S.
Abstract: Vitamin K2 (vit K2 ) belongs to a large group of fat-soluble compounds whose formulation is MK (menaquinone) (MK-2 to MK-14), that seem to be involved in different biological functions. In particular, vit K2 has been recently recognized as efficacious and safe in treatment of bone loss, as it contributes to structural integrity of osteocalcin (OC), the major non-collagenous protein typically found in bone matrix. Several studies proved low vit K2 intake is linked to bone loss and to increased fracture risk in both sexes. Nowadays, vit K2 supplementation is considered a significant manner to enhance the association of calcium and vitamin D whose role on bone health is largely recognized. On the other hand, vit K2 may be used alone or with other drugs to preserve bone quality/strength from skeletal degradation after menopause and/or in patients affected by secondary osteoporosis. In this paper, we review the most recent data about vit K2 on skeleton.